Survey of Professional forecasters 2023 - Singapore Management University (Institutional Knowledge at Singapore Management University, 2023)
Forecasters Maintain Their Expectations for Growth in 2023 The forecasters see the U.S. economy in 2023 expanding at the same pace as they predicted three months ago, according to 38 panelists surveyed by the Federal Reserve Bank of Philadelphia. The forecasters predict annual-average over annualaverage growth in real GDP of 1.3 percent in 2023, unrevised from their estimate of three months ago. The panelists are also maintaining their forecast for growth in the second quarter at an annual rate of 1.0 percent, unchanged compared with their previous projection. However, while their predictions for the second quarter and for 2023 remain the same, the forecasters revised upward their predictions for the third quarter of 2023. They also revised downward their fourth-quarter estimates.